2001
DOI: 10.1007/s004420100760
|View full text |Cite
|
Sign up to set email alerts
|

On the direct effect of clouds and atmospheric particles on the productivity and structure of vegetation

Abstract: The volume of shade within vegetation canopies is reduced by more than an order of magnitude on cloudy and/or very hazy days compared to clear sunny days because of an increase in the diffuse fraction of the solar radiance. Here we show that vegetation is directly sensitive to changes in the diffuse fraction and we conclude that the productivity and structure of vegetation is strongly influenced by clouds and other atmospheric particles. We also propose that the unexpected decline in atmospheric [CO] which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
361
2
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(395 citation statements)
references
References 53 publications
(79 reference statements)
21
361
2
11
Order By: Relevance
“…It was proposed that the increase in diffuse radiation caused by the injected stratospheric sulfate aerosols could have enhanced terrestrial photosynthesis (Roderick et al, 2001;Gu et al, 2003;Steiner and Chameides, 2005;Knohl and Baldocchi, 2008). Plant canopies may use diffuse radiation more efficiently than they use direct beam radiation in photosynthesis.…”
Section: Uncertainty Of the Modelingmentioning
confidence: 99%
“…It was proposed that the increase in diffuse radiation caused by the injected stratospheric sulfate aerosols could have enhanced terrestrial photosynthesis (Roderick et al, 2001;Gu et al, 2003;Steiner and Chameides, 2005;Knohl and Baldocchi, 2008). Plant canopies may use diffuse radiation more efficiently than they use direct beam radiation in photosynthesis.…”
Section: Uncertainty Of the Modelingmentioning
confidence: 99%
“…Alternatively, the reduction in total solar radiation is likely to be accompanied by an increase in diffuse solar radiation (Stanhill & Cohen 2001). Theoretically, this is expected to increase total canopy photosynthesis, as diffuse light can penetrate deeper into a canopy by reducing the self-shading of leaves in the canopy (Roderick et al 2001). This effect-that plant canopies can use diffuse radiation more efficiently than direct radiation-has been demonstrated in a North American hardwood forest using measurements before and after the 1991 Mt Pinatubo volcanic eruption, which in 1992 decreased global direct solar irradiance by ca.…”
Section: (Iv) Temperature and Ontogenetic Developmentmentioning
confidence: 99%
“…Several researchers have suggested that the diffuse radiation proportion in the solar radiation can result in higher light use efficiency than direct radiation (Goudriaan, 1977;Gu et al, 2002Gu et al, , 2003Roderick et al, 2001). It is well known that changes in cloud cover or atmospheric aerosol loadings, arising from either volcanic or anthropogenic emissions, alter both the total solar radiation reaching the surface and the fraction of diffuse radiation, with uncertain overall effects on global plant productivity and the land carbon sink (Mercado et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Under cloudy conditions and with aerosol loading, there is broad consensus on the impact of diffuse radiation on terrestrial ecosystem carbon cycle (Fitzjarrald et al, 1995;Gu et al, 1999;Roderick et al, 2001;Niyogi et al, 2004;Oliveira et al, 2007), especially for the North American forests. However, the relationship between clouds and ecosystem CO 2 exchange can be more complicated, due to changes in other environmental factors that could influence the ecosystem carbon cycle.…”
Section: Introductionmentioning
confidence: 99%